The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11120-015-0177-y
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the presence of key chlorophyll-biosynthesis-related proteins in the genus Rubrobacter (Phylum Actinobacteria) and its implications for the evolution and origin of photosynthesis

Abstract: Homologs showing high degree of sequence similarity to the three subunits of the protochlorophyllide oxidoreductase enzyme complex (viz. BchL, BchN, and BchB), which carries out a central role in chlorophyll-bacteriochlorophyll (Bchl) biosynthesis, are uniquely found in photosynthetic organisms. The results of BLAST searches and homology modeling presented here show that proteins exhibiting a high degree of sequence and structural similarity to the BchB and BchN proteins are also present in organisms from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 81 publications
(152 reference statements)
0
20
0
Order By: Relevance
“…We found a wide variety of carbohydrate-active enzymes in these MAGs, such as cellulases (GH1 family) in addition to genes for glycolysis and TCA cycle and a chlorophyll/bacteriochlorophyll a/b synthase ( bchG gene). The latter was also found in other Actinobacteria from the genus Rubrobacter [ 39 ]. No evidence was found for nitrile-degrading potential.…”
Section: Resultsmentioning
confidence: 64%
“…We found a wide variety of carbohydrate-active enzymes in these MAGs, such as cellulases (GH1 family) in addition to genes for glycolysis and TCA cycle and a chlorophyll/bacteriochlorophyll a/b synthase ( bchG gene). The latter was also found in other Actinobacteria from the genus Rubrobacter [ 39 ]. No evidence was found for nitrile-degrading potential.…”
Section: Resultsmentioning
confidence: 64%
“…It is overall very similar to other phylogenomic trees, and the relationship of phyla containing phototrophic strains is virtually identical to those presented before, see for example Jun et al [ 20 ], who implemented an alignment free approach. The phyla of bacteria highlighted in color represent those with photochemical reaction centers, with the exception of Actinobacteria that only recently was suggested to have been ancestrally phototrophic [ 2 ]. The colored transparent lines that are overlaid on top of the phylogenomic tree represent the evolution of the selected proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Because of these adaptations to land habitats, Battistuzzi et al called this supergroup Terrabacteria; and the supergroup that contained Proteobacteria, Acidobacteria, Chlorobi, and closely related non-phototrophic groups, Hydrobacteria [ 19 ]. Taking into account that both Chloroflexi and Cyanobacteria are capable of photosynthesis, and adding to this the possibility that Actinobacteria was ancestrally capable of photosynthesis [ 2 ], it starts to look increasingly likely that this supergroup was also ancestrally phototrophic. There is a common unifying characteristic between these two supergroups: Type I and Type II reaction centers are found in both of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within Bacteria, there are currently seven phyla known to have strains with reaction centers, these are: Cyanobacteria, Chloroflexi, Firmicutes, Chlorobi, Proteobacteria, and those recently found in Acidobacteria (Bryant et al, 2007 ; Tsukatani et al, 2012 ) and Gemmatimonadetes (Zeng et al, 2014 , 2015 ). Just a while ago, it was suggested that the phylum Actinobacteria might have been ancestrally capable of photosynthesis (Gupta and Khadka, 2016 ), as some strains in this phylum seem to have a vestigial chlorophyll synthesis pathway. Although a consensus on the type of bacteria in which photochemical reaction centers originated is lacking, it is understood that both Type I and Type II reaction centers have a common origin.…”
Section: Evolution Of Reaction Center Proteinsmentioning
confidence: 99%